Effectiveness of Online Tools for First Generation Business Start-ups Sustainability in Satara. Issue 1 (March 2019) - Tatpuje, Dipak U.; Ganbote, Avinash
Entrepreneurship Education, Information Technology (IT) education, training, mentoring and post-training support is necessary to empower the rural youths for the establishment of their start-ups. Use of 'IT' in the business activity is now needed to cross geographical boundaries for its potential market. In this research, investigator studied effectiveness of various online tools and its impact upon the sustainability in terms of revenue generation of the business started by the youth in Satara. It is specifically related to rise in the rate of sale with the use of online tools. In this study, it is observed that well-organized training is found useful for capacity building of rural youth entrepreneurs and revenue generation in their start-ups through interventions of IT tools. During the training of participants of experimental group, market place simulations, IT product development, digital marketing and online platforms are found to be effective with social media platforms. It is for the interactive tele-collaboration and to develop latest skills with responsive webs, mobile and web apps. It is found useful to attract potential customers to the start-ups of the experimental group participants as compared to the start-ups of the participants of the control group.